Targeting Ferroptosis to Treat Cardiovascular Diseases: A New Continent to Be Explored - Huang, Fangze; Yang, Ronghua; Xiao, Zezhou; Xie, Yu; Lin, Xuefeng; Zhu, Peng; Zhou, Pengyu; Lu, Jun; Zheng, Shaoyi (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular diseases, including cardiomyopathy, myocardial infarction, myocardial ischemia/reperfusion injury, heart failure, vascular injury, stroke, and arrhythmia, are correlated with cardiac and vascular cell death. Ferroptosis is a novel form of non-apoptotic regulated cell death which is characterized by an iron-driven accumulation of lethal lipid hydroperoxides. The initiation and execution of ferroptosis are under the control of several mechanisms, including iron metabolism, glutamine metabolism, and lipid peroxidation. Recently, emerging evidence has demonstrated that ferroptosis can play an essential role in the development of various cardiovascular diseases. Recent researches have shown the ferroptosis inhibitors, iron chelators, genetic manipulations, and antioxidants can alleviate myocardial injury by blocking ferroptosis pathway. In this review, we systematically described the mechanisms of ferroptosis and discussed the role of ferroptosis as a novel therapeutic strategy in the treatment of cardiovascular diseases.